Analisis Yuridis Terhadap Perlindungan Hukum Korban Yang Melakukan Pembelaan Terpaksa - Fadhlullah, Rouf; Maulani, Diah Gustiniati; Monica, Dona Raisa; Raharjo, Eko (Indonesian Journal Publisher, 2025)
This research aims to provide an overview of Legal Protection for Victims Who Act in Self-Defense. In this study, the author employs a normative juridical approach. The theoretical framework used is the Theory of Factors Influencing Law Enforcement, by examining the obstacles that affect law enforcement in cases where victims attempt to defend themselves. The secondary data used in this research is sourced from various materials such as statutory regulations and legal journals. The findings show that the Indonesian Criminal Code (KUHP) regulates self-defense (noodweer) and excessive self-defense (noodweer exces) as stipulated in Article 49 paragraph (1) and paragraph (2) of the KUHP. Article 49 serves as the legal basis for providing legal protection to individuals who act in self-defense. Under this Article, a criminal act committed may be exempted from criminal liability, allowing the perpetrator to be free from any legal charges, provided that the elements of self-defense are fulfilled. Obstacles in law enforcement for cases involving self-defense include unclear legal provisions, limited understanding among law enforcement officers of the noodweer concept, lack of supporting infrastructure such as CCTV, low public awareness in reporting crimes, and a weak legal culture. Of all the factors, law enforcement is considered the most dominant because the central role of officers in enforcing regulations professionally, objectively, and fairly is crucial in determining the true realization of justice.